2022
DOI: 10.4018/978-1-7998-7271-9.ch004
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review on the Neuro-Cognitive Correlates of Game-Based Learning in Higher Education Learning Environments

Abstract: Game-based learning is one of the sustainable education methods for future professionals from the higher education learning environment. To attain these innovative and sustainable teaching pedagogies, the components of games and simulations need to be incorporated into the teaching-learning content. The integration of neuroscience and cognitive concepts has become an essential feature in understanding various phenomena in game-based learning with regard to higher education learning environments. Several neural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…The items are measured using a five-point Likert-type scale ranging from 1 = "totally disagree" to 5 = "totally agree. " This scale measures the experience of play based on prior research (Smith and Vollstedt, 1985;Baboo et al, 2022). Higher scores…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The items are measured using a five-point Likert-type scale ranging from 1 = "totally disagree" to 5 = "totally agree. " This scale measures the experience of play based on prior research (Smith and Vollstedt, 1985;Baboo et al, 2022). Higher scores…”
Section: Methodsmentioning
confidence: 99%
“…The experience of play comprises three dimensions, including enjoyment (e.g., “Did you enjoy the process of play?”), learning (e.g., “Did you learn new knowledge while you were playing?”), and new skills (e.g., “Did you learn new skills while you were playing?”). The items are measured using a five-point Likert-type scale ranging from 1 = “ totally disagree ” to 5 = “ totally agree .” This scale measures the experience of play based on prior research ( Smith and Vollstedt, 1985 ; Baboo et al, 2022 ). Higher scores indicate higher levels of positive play experience.…”
Section: Methodsmentioning
confidence: 99%
“…The corporate sector increased used of games in pre-employment evaluation, assessment, and business simulations. In the academic sector, DGBL is recognized as a successful approach for teaching the 21st-century skills (Baboo et al, 2022) to support a wide variety of higher-order cognitive skills in complex decision-making contexts (De Freitas & Jarvis, 2007;Gee 2005). Keller (1999) reported that a lack of motivation is a major cause of student attrition.…”
Section: Chapter 1 -Introductionmentioning
confidence: 99%